FGF19 and FGF21 for the Treatment of NASH—Two Sides of the Same Coin? Differential and Overlapping Effects of FGF19 and FGF21 From Mice to Human - Henriksson, Emma; Andersen, Birgitte (Frontiers in Endocrinology, 2020)
FGF19 and FGF21 analogues are currently in clinical development for the potential treatment of NASH. In Phase 2 clinical trials analogues of FGF19 and FGF21 decrease hepatic steatosis with up to 70% (MRI-PDFF) after 12 weeks and as early as 12–16 weeks of treatment an improvement in NASH resolution and fibrosis has been observed. Therefore, this class of compounds is currently of great interest in the field of NASH. FGF19 and FGF21 belong to the endocrine FGF19 subfamily and both require the co-receptor beta-klotho for binding and signalling through the FGF receptors. FGF19 is expressed in the ileal enterocytes and is released into the enterohepatic circulation in response to bile acids stimuli and in the liver FGF19 inhibits hepatic bile acids synthesis by transcriptional regulation of Cyp7A1, which is the rate limiting enzyme. FGF21 is, on the other hand, highly expressed in the liver and is released in response to high glucose, high free-fatty acids and low amino-acid supply and regulates energy, glucose and lipid homeostasis by actions in the CNS and in the adipose tissue. FGF19 and FGF21 are differentially expressed, have distinct target tissues and separate physiological functions. It is therefore of peculiar interest to understand why treatment with both FGF19 and FGF21 analogues have strong beneficial effects on NASH parameters in mice and human and whether the mode of action is overlapping This review will highlight the physiological and pharmacological effects of FGF19 and FGF21. The potential mode of action behind the anti-steatotic, anti-inflammatory and anti-fibrotic effects of FGF19 and FGF21 will be discussed. Finally, development of drugs is always a risk benefit analysis and the human relevance of adverse effects observed in pre-clinical species as well as findings in humans will be discussed. The aim is to provide a comprehensive overview of the current understanding of this drug class for the potential treatment of NASH.